(untitled) (Journal of the College of Basic Education, 2023)
Industrial activity is considered one of the most important aspects of economic activity for any country, and its great contribution to the national income in addition to providing job opportunities. From construction movements and urban expansion, in addition to an increase in demand for road paving and street paving, such as roads, bridges, hospitals, buildings, housing projects and other economic projects, including industrial ones, and the accompanying other projects that depend on building materials in their construction operations. The main objective of this study is to present the historical development of the slabs industry in the study area and analyze the factors from the natural and human geographic components, and then determine the geographical distribution in the judiciary. We have come up with a number of things. The slab industry is considered one of the important industries in the study area, until the beginning of the eighties of the twentieth century, but it developed significantly after 2004, especially after the development of the cities and districts of Ramadi and Fallujah.